Glutathione peroxidase 7 knockdown inhibits growth, invasion, and migration while enhancing oxidative stress and ferroptosis in osteosarcoma cells - Runze He; Xiao Xiao; Xinwen Tang; Chen Lv (Journal of Bone Oncology)
Background: Glutathione peroxidase 7 (GPX7) possesses antioxidant functions and plays a crucial role in regulating cancer progression. However, relevant evidence in osteosarcoma is scarce. The current study aimed to explore the effect of GPX7 on osteosarcoma progression, oxidative stress, and ferroptosis. Methods: Human osteosarcoma cells (U2OS, MG-63, and SaOS-2) were transfected with GPX7 small interfering RNA (siGPX7). Proliferation, apoptosis, invasion, migration, oxidative stress markers, Fe2+ levels, and ferroptosis markers were detected in human osteosarcoma cells. Results: GPX7 knockdown inhibited human osteosarcoma cell proliferation, as evidenced by reduced relative cell viability and 5-Ethynyl-2′-deoxyuridine positive cells. GPX7 knockdown also showed a certain ability to promote human osteosarcoma cell apoptosis, as evidenced by increased terminal-deoxynucleotidyl transferase-mediated nick end labeling (TUNEL) positive rate and cleaved-caspase3. GPX7 knockdown decreased invasive and migration rates of human osteosarcoma cells. GPX7 knockdown increased reactive oxygen species and malondialdehyde but decreased mitochondrial membrane potential, suggesting that GPX7 knockdown enhanced oxidative stress in human osteosarcoma cells. Regarding ferroptosis markers, GPX7 knockdown increased acyl-CoA synthetase long-chain family member 4 and reduced solute carrier family 7 member 11; moreover, GPX7 knockdown increased Fe2+ levels; the above findings indicated that GPX7 knockdown promoted ferroptosis in human osteosarcoma cells. Conclusion: GPX7 knockdown inhibits osteosarcoma cell growth, invasion, and migration while facilitating oxidative stress and ferroptosis.